2017
DOI: 10.7554/elife.31649
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling via Gli2 prevents obesity induced by high-fat diet in adult mice

Abstract: Obesity poses a significant risk of developing type II diabetes and other diseases. Hedgehog (Hh) signaling has been shown to inhibit adipose tissue development, but its effect on diet-induced obesity during postnatal life is not known. Here by inducing expression of constitutively active Smoothened (SmoM2) or Gli2 (ΔNGli2) in the adipocyte lineage of postnatal mice, we show that targeted activation of Hh signaling suppresses high-fat-diet-induced obesity and improves whole-body glucose tolerance and insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…This signalling pathway involves the binding of extracellular Hh protein to a cell surface receptor complex consisting of Patched (Ptch) and Smoothened (Smo). Smo then activates a cascade of intracellular signals resulting in the activation of target genes by Gli family transcription factors (Gli 1, 2, and 3) [75]. Adipocyte differentiation is prevented through the specific inhibition of C/EBPα and PPARγ [35].…”
Section: Hedgehog Signalling Pathwaymentioning
confidence: 99%
“…This signalling pathway involves the binding of extracellular Hh protein to a cell surface receptor complex consisting of Patched (Ptch) and Smoothened (Smo). Smo then activates a cascade of intracellular signals resulting in the activation of target genes by Gli family transcription factors (Gli 1, 2, and 3) [75]. Adipocyte differentiation is prevented through the specific inhibition of C/EBPα and PPARγ [35].…”
Section: Hedgehog Signalling Pathwaymentioning
confidence: 99%
“…Shh inhibits adipocyte differentiation by diverting preadipocytes away from adipogenesis (15), which is implicated in the development of white adipose tissue (16). The Hh-Gli2 axis drives lipogenesis in adipocytes, leading to increased obesity in adult mice (17). Moreover, Shh-related ciliopathy is involved in obesity, cognitive impairment, and limb deformities, which has been defined as Bardet-Biedl syndrome in humans (18).…”
mentioning
confidence: 99%
“…In this study, we found that LAMA2 regulates osteogenesis and adipogenesis of MSCs via modulating the hedgehog signaling pathway. The hedgehog signaling pathway is involved in bone formation and in osteogenic and adipogenic differentiation of MSCs which indicates that targeted regulation of hedgehog signaling is a potential target for the treatment of bonerelated diseases such as osteoporosis and fracture healing [19,20,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%